Analysis of the Implementation of Good Corporate Governance in Enhancing Company Performance at PT Kawasan Industri Makassar (KIMA) - Sarmila Sarmila; Idil Rakhmat Susanto; Mellisyah Mellisyah (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Good Corporate Governance (GCG) has become an essential mechanism for strengthening organizational effectiveness, enhancing stakeholder trust, and supporting sustainable business performance, particularly in industrial estate management companies that operate within complex governance environments. Despite the growing importance of governance practices, empirical studies focusing on industrial estate companies remain limited compared to those conducted in the banking and service sectors. This research explores the implementation of GCG principles at PT Kawasan Industri Makassar (KIMA) and examines their contribution to company performance. A descriptive qualitative approach was employed using primary and secondary data collected through interviews, observations, documentation, and data triangulation. Informants consisted of personnel directly involved in governance implementation, including representatives from the corporate governance division and the Internal Audit Unit. The findings indicate that the principles of transparency, accountability, responsibility, independence, and fairness have been implemented through governance guidelines, internal control systems, and organizational supervision mechanisms. These practices contribute to improved operational effectiveness, stronger internal control, enhanced decision-making quality, and increased stakeholder confidence. However, several challenges remain, including uneven employee understanding of governance principles, limited information transparency, and the need for more intensive governance training and evaluation systems. The findings contribute to the development of corporate governance literature by providing empirical evidence from the industrial estate sector and highlighting practical strategies for strengthening governance effectiveness in similar organizations.